Molecular dynamics simulations of shock-compressed single-crystal silicon - Mogni, G; Higginbotham, A; Gaal-Nagy, K; Park, N; Wark, J (2014)
We present molecular dynamics simulations using a Tersoff-like potential of single crystals of silicon shock compressed along the O001 O direction. We find an elastic response up to a critical stress, above which the shear stress is relieved by an inelastic response associated with a partial transformation to a new high-pressure phase, where both the new phase (Imma) and the original cubic diamond phase are under close to hydrostatic conditions. We study how the fraction of the two phases is related to both their geometry and their enthalpy, and discuss the relevance of the results to previous experimental measurements of the response of silicon to shock compression. We note that the simulations are consistent with shear stress relief provided directly by the shock-induced phase transition itself, without an intermediate state of plastic deformation of the cubic diamond phase, but that the onset of inelastic behavior within the simulations still occurs at considerably higher stresses than found in experiments. © 2014 American Physical Society.